12‐Channel Peltier array temperature control unit for single molecule enzymology studies using capillary electrophoresis. Issue 16 (25th March 2014) - Craig, Douglas B.; Reinfelds, Gundars; Henderson, Anna; Garcia, Carlos D.; Carrilho, Emanuel
<x xml:space="preserve">Abstract</x> Capillary electrophoresis has been used to demonstrate that individual molecules of a given enzyme support different catalytic rates. In order to determine how rate varies with temperature, and determine activation energies for individual β‐galactosidase molecules, a 12‐channel Peltier array temperature control device was constructed where the temperature of each cell was separately controlled. This array was used to control the temperature of the central 30 cm of a 50 cm long capillary, producing a temperature gradient along its length. Continuous flow single β‐galactosidase molecule assays were performed allowing measurement of the catalytic rates at different temperatures. Arrhenius plots were produced and the distribution of activation energies for individual β‐galactosidase molecules was found to be 56 ± 10 kJ/mol with a range of 34–72 kJ/mol.